Comparison of olmesartan combined with a calcium channel blocker or a diuretic in elderly hypertensive patients (COLM Study): safety and tolerability - Saruta, Takao (Hypertens Res, 2015)
The cardiovascular effects of combined therapy with the angiotensin receptor blocker (olmesartan) and a dihydropyridine calcium channel blocker (CCB) or a diuretic were compared in high-risk elderly Japanese hypertensive patients by performing a randomized, open label, blinded-endpoint study of morbidity and mortality (the COLM study). Here we report the results obtained with respect to safety and tolerability. High-risk hypertensive patients aged 65–84 years were enrolled and were randomized to receive olmesartan combined with either a CCB (amlodipine or azelnidipine) or a low-dose diuretic for at least 3 years. The primary endpoint was a composite of fatal and non fatal cardiovascular events, whereas adverse events (AEs) and the percentage of patients who discontinued the allocated treatment were evaluated as secondary endpoints. A total of 5141 patients were randomized. Both combination regimens achieved a similar reduction of cardiovascular morbidity and mortality. The incidences of AEs, serious AEs, drug-related serious AEs and discontinuation due to serious AEs were lower in the olmesartan plus CCB group than in the olmesartan plus diuretic group. Serum levels of uric acid and creatinine were significantly higher in the olmesartan plus diuretic group than in the olmesartan plus CCB group. Olmesartan combined with a CCB was significantly superior to olmesartan plus a diuretic with regard to the frequency of AEs and discontinuation of treatment.